Tests on the Mechanical Properties of Corroded Cement Mortar after High Temperature - Liang-Xiao, Xiong; Cong, Chen (Salehan Institute of Higher Education, 2020)
Durability of cement mortar and concrete materials under sea water condition is always an important research topic. The objective of this work is to understand the mechanical properties of corroded cement mortar after high temperature, the cement mortar specimens after high temperature were placed in water and sodium sulfate solution, and then the uniaxial compression tests were carried out on the cement mortar specimens after corroded. Test results show that both the differences of compressive strength and strain at the peak stress after high temperature caused by high temperature, are relatively small when the specimens are eroded in water, and the differences are relatively high when the specimens are eroded in sodium sulfate solution. The compressive strength of the cement mortar specimens under normal temperature eroded in sodium sulfate solution is highest, and that eroded in water is lowest. The compressive strength of specimen after high temperature eroded in water is highest and that eroded in sodium sulfate solution is lowest. The strain at the peak stress of specimen, whether after high temperature or not, is highest when eroded in sodium sulfate solution, and that eroded in water is lowest. At present, there are few research results about the mechanical properties of concrete first after high temperature and then after sea water corrosion. The work in this paper can enrich the results in this area.